2015
DOI: 10.1515/nuka-2015-0020
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of heat capacity and Mössbauer data for LuZnSn2 compound

Abstract: Abstract. New analysis of heat capacity data is presented for LuZnSn 2 compound that takes into account anharmonic effects together with the existence of Einstein modes. Sn Mössbauer spectroscopy was used to monitor the hyperfi ne parameters at the two crystallographically inequivalent Sn sites in the studied compound. The problem of non-unique mathematical resonance spectrum description and the problem how to choose physically meaningful set of hyperfi ne parameters will be thoroughly discussed. Measured quad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…However, it was shown that the experimental heat capacity data, C lat (T), for LuZnSn 2 [24] and ErZnSn 2 , as expounded in this work, can be successfully fi tted over the whole temperature range by taking into account anharmonic effects that occur at elevated temperatures, as well as by the inclusion of selected Einstein modes for LuZnSn 2 and ErZnSn 2 respectively using the extended Debye equation in the form:…”
Section: Heat Capacitymentioning
confidence: 99%
See 2 more Smart Citations
“…However, it was shown that the experimental heat capacity data, C lat (T), for LuZnSn 2 [24] and ErZnSn 2 , as expounded in this work, can be successfully fi tted over the whole temperature range by taking into account anharmonic effects that occur at elevated temperatures, as well as by the inclusion of selected Einstein modes for LuZnSn 2 and ErZnSn 2 respectively using the extended Debye equation in the form:…”
Section: Heat Capacitymentioning
confidence: 99%
“…2a and 2c sites, the spectrum recorded at room temperature can be reasonably fi tted with two quadrupole-split components including a single line of the metallic impurity tin (with isomer shift  IS kept constant and equal to 2.552(9) mm/s [25]), which is also evident from X-ray diffraction analysis and originates from the synthesis procedure as well as the known decomposition process of the probe over time. Similarly to the case of LuZnSn 2 [24], the resonance spectrum recorded for ErZnSn 2 at room temperature can be fi tted with different pairs of main quadrupole split subsets of hyperfi ne parameters (together with the respective pairs of isomer shifts) for two crystallographically inequivalent Sn sites. However, from a physical point of view, a fi t with only two different quadrupole interaction constants and comparable isomer shifts for both Sn sites (Fig.…”
Section: Sn Mössbauer Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation